- The Effect of Principal’s Leadership and School Culture Through Word Ethic Against Teacher Professionalism - Laily, Nur; Suminar, Tri; Yulianto, Arif (Educational Management, 2021)
In the 21st-century professional competence of teachers is needed in carrying out the teaching and learning process, which is pursued through the Development of Sustainable Profession (CLA). The low level of CLA in SMP Negeri 1 Semarang proves that the government's efforts to improve teacher professionalism haven’t been successful. This study aims to determine the effect of principal leadership and school culture through work ethic on the professionalism of junior high school teachers in Semarang City. This study applies the analysis path through two regression analyses: 1) regression analysis between principal leadership, school culture, and work ethic on teacher professionalism, and 2) regression analysis between principal leadership and school culture on work ethic. This study uses the online Sobel Test Calculator to test the variables. The results of the regression analysis stated that the principal's leadership had no direct effect on teacher professionalism. Principal leadership and school culture affect teacher professionalism through work ethic as an intervening variable according to the results of the Sobel test.